Genotypic covariations of traits underlying sorghum stem biomass production and quality and their regulations by water availability: Insight from studies at organ and tissue levels. Issue 2 (25th October 2018) - Luquet, Delphine; Perrier, Lisa; Clément‐Vidal, Anne; Jaffuel, Sylvie; Verdeil, Jean‐Luc; Roques, Sandrine; Soutiras, Armelle; Baptiste, Christelle; Fabre, Denis; Bastianelli, Denis; Bonnal, Laurent; Sartre, Pascal; et al.
Abstract: Sweet and biomass sorghum are expected to contribute increasingly to bioenergy production. Better understanding the impacts of the genotypic and environmental variabilities on biomass component traits and their properties is essential to optimize energy yields. This study aimed to evaluate whether traits contributing to stem biomass growth and biochemical composition at different biological scales (co)vary with the genotype and the water status in sorghum. Height genotypes were studied over two years in field conditions in southern France under two water treatments (well watered vs. 25 days' dry down during stem elongation). Main stem internode number, size, (non)structural carbohydrate, and lignin contents were measured at the end of the stress period and/or at final harvest, together with biochemical and histological analyses of the youngest expanded internode. The tallest genotypes showed the highest stem dry weights and lignin contents. Stem (structural) biomass density was positively correlated with lignin content, particularly in internode parenchyma. Stem soluble sugar and lignin contents were inversely proportional across genotypes and water conditions. Genotypes contrasted for drought sensitivity and recovery capacity of stem growth and biochemical composition. The length and cell wall deposition of internodes expanding under water deficit were reduced and did not recover, these responses being weakly correlated. Genotypic variability was pointed out in the growth recovery of internodes expanding under re‐watered conditions. According to the observed genotypic variability and the absence of antagonistic correlations between the responses of the different traits to water availability, it is suggested that biomass sorghum varieties optimizing their responses to water availability in terms of growth and cell wall deposition can be developed for different bioenergy targets. Abstract : (a) Relation between stem lignin content (ADL) and height (PHT) or sugar content (NIRS prediction: SUG). (b) PCA for stem morphological variables (PHT, leaf number LIG, density of total and structural stem biomass: respectively Dens and Dens_Str, in g/cm3) and internode variables: morphological (length, diameter), histological (percentage of red tissue in inner zone Z2 (%RedZ2) and outer zone Z1 (%RedZ1), percentage of Z1 area (%Z1), density of vascular bundles in Z2 (VZ2, mm−2), biochemical (Lignin and soluble sugar SS contents in mg/g of DW), and NIRS prediction of cellulose content (CELL %DW). Internode variables refer to the second internode below the flag leaf phytomer on the main stem and are indicated in italics in (b). The two‐first dimensions (Dim 1 and Dim 2) of the PCA are considered. The centroid for each genotype is positioned (black circles). Below the PCA are presented the contributions (%) of each variable and the Cos² of each genotype on Dim 1 and Dim 2. The size and darkness of circles for each factor refer to the scale on the right. (c) Relation between stem Dens_str and %RedZ2 or Lignin content in IN‐2. Data from the well watered treatment at final harvest in 2014 and 2015 for the eight studied genotypes. Each point in (a) and (c) is the average of three blocks per genotype and year.